The Oxford handbook of Islamic philosophy - El-Rouayheb, Khaled; Schmidtke, Sabine (New York : Oxford University Press, 2017)
A study of Islamic philosophy has entered a new and exciting phase in the last few years. Both the received canon of Islamic philosophers and the narrative of the course of Islamic philosophy are in the process of being radically questioned and revised. Most twentieth-century Westernscholarship on Arabic or Islamic philosophy has focused on the period from the ninth century to the twelfth. It is a measure of the transformation that is currently underway in the field that, unlike other reference works, the Oxford Handbook has striven to give roughly equal weight to everycentury, from the ninth to the twentieth. The Handbook is also unique in that its 30 chapters are work-centered rather than person- or theme-centered, in particular taking advantage of recent new editions and translations that have renewed interest and debate around the Islamic philosophical canon.The Oxford Handbook of Islamic Philosophy gives both the advanced student and active scholar in Islamic philosophy, theology, and intellectual history, a strong sense of what a work in Islamic philosophy looks like and a deep view of the issues, concepts, and arguments that are at stake. Mostimportantly, it provides an up-to-date portrait of contemporary scholarship on Islamic philosophy.
Includes bibliographical references and indexes.
Keywords: Islamic philosophy